Single-Cell Transcriptome Analysis Reveals Six Subpopulations Reflecting Distinct Cellular Fates in Senescent Mouse Embryonic Fibroblasts - Chen, Wei; Wang, Xuefei; Wei, Gang; Huang, Yin; Shi, Yufang; Li, Dan; Qiu, Shengnu; Zhou, Bin; Cao, Junhong; Chen, Meng; Qin, Pengfei; Jin, Wenfei; et al. (Frontiers in Genetics, 2020)
Replicative senescence is a hallmark of aging, which also contributes to individual aging. Mouse embryonic fibroblasts (MEFs) provide a convenient replicative senescence model. However, the heterogeneity of single MEFs during cellular senescence has remained unclear. Here, we conducted single-cell RNA sequencing on senescent MEFs. Principal component analysis showed obvious heterogeneity among these MEFs such that they could be divided into six subpopulations. Three types of gene expression analysis revealed distinct expression features of these six subpopulations. Trajectory analysis revealed three distinct lineages during MEF senescence. In the main lineage, some senescence-associated secretory phenotypes were upregulated in a subset of cells from senescent clusters, which could not be distinguished in a previous bulk study. In the other two lineages, a possibility of escape from cell cycle arrest and coupling between translation-related genes and ATP synthesis-related genes were also discovered. Additionally, we found co-expression of transcription factor HOXD8 coding gene and its potential target genes in the main lineage. Overexpression of Hoxd8 led to senescence-associated phenotypes, suggesting HOXD8 is a new regulator of MEFs senescence. Together, our single cell sequencing on senescent MEFs largely expanded the knowledge of a basic cell model for aging research.